Implementasi Ekonomi Syariah dalam Administrasi Pembangunan di Indonesia pada Era Transformasi Digitalisasi - Hanif Ibrahim; Moh Mukhsin (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
The implementation of Islamic economics in Indonesia's development administration during the digital era presents a significant opportunity to build a system founded on inclusivity, fairness, and sustainability. Digital transformation plays a pivotal role in optimizing sharia-based financial technologies, empowering community economies, and enhancing resource management efficiency. Technologies such as halal e-commerce, blockchain, and sharia-compliant financial applications extend access to financial services in previously underserved remote areas. However, challenges such as low digital literacy levels and insufficient regulatory frameworks remain obstacles. Collaboration among the government, Islamic financial institutions, businesses, and communities is essential to ensure the effective implementation of this system. By combining sharia principles with technological innovations, Islamic economics holds substantial potential to boost Indonesia's economic competitiveness on a global scale.